Peningkatan Kemampuan Mengenal Angka Melalui Penggunaan Media Kartu Wayang Pada Anak Usia Dini - Uswatun Hasanah; M. Rusdi T; Wahyuni Ismail; Susniawan Susniawan; Ade Agusriani (Early Childhood Islamic Education, 2023)
This study aims to describe the ability to recognize numbers in children before the application of wayang card media, to describe the ability to recognize numbers in children after the application of wayang card media, and to find out differences in the ability to recognize numbers through the use of wayang card media in early childhood at Yaspib Pertiwi Kindergarten, Bontolempangang District. This type of research is descriptive quantitative, using saturated sampling. The number of samples taken was all group A students of Yaspib Pertiwi Kindergarten, Bontolempangang District. The research instruments used were observation sheets, test sheets, and checklists. Data analysis techniques using descriptive data analysis. The results of the descriptive test show that the ability to recognize numbers before applying the wayang card media too early childhood obtains an average value of 6, the ability to recognize numbers after the application of wayang card media obtains an average value of 12, and there is a difference in the average ability get to know numbers in children aged in Kindergarten Yaspib Pertiwi, Bontolempangang District after applying the wayang card media. The implications of this research are expected to be able to add insight to children in knowing numbers, educators can apply wayang card media in learning activities, and can be an initial reference for researchers.